A pilot investigation examining systemic inflammation in pediatric chronic pain patients. (September 2021) - Kim, A.J.; Bento, S.; Enlow, M. Bosquet; Nelson, S.
Abstract : Background: Pediatric chronic pain is a significant public health concern, with an estimated 25% of youth experiencing a chronic pain episode in their lifetime. Despite this prevalence, the mechanisms underlying chronic pain in youth remain poorly understood. Psychological stress and its sequalae have been proposed as contributors to pain chronicity, with the physiological stress response identified as a potential target for intervention. However, few studies have provided concrete evidence of this proposed connection. The current pilot study aimed to address this gap by investigating levels of C-reactive protein (CRP), a mechanism of stress and indicator of immune functioning, in pediatric pain patients. Methods: Youth (N = 57; ages 10-17, Mage=14.47) presenting for tertiary chronic pain treatment were asked to provide saliva for CRP assaying as an adjunct to their clinic appointment, which included measures of psychological stress, anxiety and depressive symptoms, functional disability (FDI), and pain intensity. Results: Pediatric pain patients with lower CRP evidenced higher psychological stress (Z = -2.203, p =.028) and functional disability (Z = -1.982, p =.047). Conclusions: This pilot investigation provides preliminary evidence for a decreased immunologic response in pediatric chronic pain patients who report elevated levels of stress and disability. Future research should further examine these proposed connections.